Positive cross-linguistic influence in the representation and processing of sentence-final particle le by L2 and heritage learners of Chinese - Yan, Shanshan; Mai, Ziyin; Zhao, Yang (Frontiers in Psychology, 2023)
This study investigates the representation and processing of written Chinese sentences subject to a semantic condition (i.e., “direction of change”) attached to the sentence-final particle (SFP) le in Mandarin Chinese. Three groups of bilingual speakers of Chinese and English who differ in their onset age of bilingualism and proficiency of English were studied. It was anticipated that there would be a positive cross-linguistic influence (CLI) from English due to similarities between the SFP le and the English adverb already in terms of direct semantic transfer. An acceptability judgment (AJ) task and a self-paced reading (SPR) task were conducted to elicit judgment and processing difficulty with and without semantic violations. The participants included English-dominant second language (L2) learners (n = 18) and heritage learners (n = 19) who had advanced proficiency in Chinese, as well as monolingually raised Mandarin speakers from China as a baseline control group (n = 18). The results indicated that sensitivity to violations of the semantic condition varied depending on factors such as the specific structure (noun vs. verb phrase), the task type (offline vs. online), and the type of bilingual speaker (early vs. late). Among the three groups of bilinguals, the heritage learners demonstrated a representation of the semantic condition that resembled the target language across different sentence structures, whereas the L2 learners did not. Furthermore, the heritage learners exhibited earlier sensitivity to violations during online processing compared to the baseline control group. These exceptional results can be attributed to the heritage learners’ early exposure to and positive CLI between the SFP le in Mandarin and the English adverb already.